Paul Goodman and the Gestalt theory of self. (1st October 2016) - Philippson, Peter
Abstract : Paul Goodman contributed to the Gestalt theory of self in a number of ways, not least by extending some of Fritz Perls' founding insights and further distancing the theory from its psychoanalytical underpinning. His seminal text Gestalt Therapy: Excitement and Growth in the Human Personality (co-authored with Perls and Ralph Hefferline, 1951) introduced the ideas of 'creative adjustment' and the 'autonomous criterion', which are central to his own, more nuanced perspective.